Sound-Oriented Textuality: The Case of Heraclitus (Revista Archai, 2021)
This paper presents the proposal to understand the remaining texts of Heraclitus' lost book as words arrangement based on audiofocal patterns. Thus, such texts would not only contain references to sounds but would also creatively explore psychoacoustic magnitudes. Basic to the argument developed here is the identification of an oscillatory movement present both in the distribution of words and sentences and in textual references. Such oscillatory movement approximates Heraclitus' writing to acoustic physical events.